Eimeria spp. infection in lambs from southern Brazil - Martins,Natália S. (2020)
ABSTRACT: Eimeria infections are common in the sheep industry worldwide. Lambs are more susceptible to coccidiosis, especially in stressful conditions, being infected by different species of the parasite. Eimeria crandallis and Eimeria ovinoidalis are considered the most pathogenic, causing reduced growth, dehydration, anorexia, and death. In this study, the frequency of Eimeria species was evaluated in lambs from the southern region of the Rio Grande do Sul state, Brazil. Fecal samples from 248 lambs, from 19 farms, were tested for the presence of oocysts. The positive samples were re-examined and the sporulated oocysts analyzed morphometrically to identify the presence of Eimeria species. In 100% of the evaluated farms, there were animals positive for the protozoan. The frequency of Eimeria species was: E. ovinoidalis (94.74%), E. crandallis (89.47%), E. granulosa (78.95%), E. parva (68.42%), E. ahsata (63.13%), E. punctata (42.11%), E. bakuensis (36.84%), E. faurei (10.53%), and E. pallida (5.26%). Mixed infection was found in 94.74% of the samples. This research describes, for the first time, the occurrence of E. crandallis and E. ovinoidalis infecting lambs in the study area. The wide distribution of this protozoan and the high frequency of pathogenic species show the importance and potential damage of sheep coccidiosis in herds from Rio Grande do Sul.